Teaching Preservation of Kemojo Cake (Bolu Kemojo) as A Traditional Cake of The Malay Community of Riau Province - Ashari, Naufal; Yogha, Sudewi; Lasmanawati, Elly (Indonesian Journal of Multidiciplinary Research, 2021)
Kemojo cake is a traditional food of the Malay people from Riau Province. In ancient times, this cake was a snack for the king and guests of the Siak kingdom, which was located in Siak Regency, Riau Province. At that time, not everyone could enjoy the Kemojo Cake because it took a very long time to make. In ancient times, Kemojo Cake was always served at weddings, traditional events, and major Islamic events. The shape of Kemojo Cake holds the symbol of Frangipani flowers. Nowadays, it is not difficult to find Kemojo Cake because many sell it, especially in the city of Pekanbaru. Now, Kemojo Cake is sold with very interesting variations with different flavors and shape modifications. Because of that, preservation by remaking the original Kemojo Cake is very important. One of the objectives of the preservation is to maintain the original Kemojo Cake so that it will not be lost and so that it will get preserved by using observation, interview, and documentation techniques. Participants in this study were divided into 3 types: Kemojo Cake experts to find out about Kemojo Cake in-depth; Kemojo Cake businessmen to prove that Kemojo Cake had been modified both in terms of taste and shape, as well as to prove the greatness of the existence of Kemojo Cake in Riau Province; and local people who traditionally make Kemojo Cake as a form of conservation effort.